Metabolic syndrome and its socio demographic and behavioral correlates: a cross sectional study among adult patients attending medicine outpatient department in a tertiary care hospital, West Bengal - Kunti, Sanjoy Kumar; Ghosh, Santanu; Samanta, Amrita; Chakraborty, Indranil (International Journal Of Community Medicine And Public Health, 2019)
Background: Metabolic syndrome (MS) is a pre-condition for cardiovascular diseases and type 2 diabetes mellitus (T2DM) which are major contributors to morbidity and mortality worldwide. Methods: The cross-sectional, observational study was conducted to estimate the proportion of MS and to explore crucial risk factors for MS among adult patients attending medicine OPD in a tertiary care hospital in West Bengal. The estimated final sample size was 315. Baseline socio demographic information and information on risk factors for MS, such as dietary habit, physical activity status, substance use, intake of related drugs, and presence of co-morbidities were collected by interviewing the patients with the help of a predesigned, pretested, structured schedule. Anthropometric measurements such as weight, height, waist circumference recordings were taken, and blood pressure was measured. Results: About 64% of the final study population (210/330) suffered from MS. On bivariate analysis, significant association between female gender (df=1, Pearson chi-square=5.06, p=0.024), weekly frequency of consumption of junk foods (df=3, Pearson chi-square=10.40, p=0.015) and obesity according to BMI (independent samples Mann-Whitney U test, p=0.010) at 5% level of significance were observed. Performing binary logistic regression analysis, obesity according to BMI (AOR=1.388, 95% CI=1.064-1.810) was found to be significant. Conclusions: Majority of the population suffered from MS who were mostly female, obese and consumers of junk foods. Appropriate interventional measures in terms of life style modification both at community and at tertiary care level are the need of the hour.